Pulsed direct current magnetron sputtered nanocrystalline tin oxide films - Reddy, A. Sivasankar (2012)
The nanocrystalline tin oxide (SnO2) films were deposited on glass substrates by pulsed magnetron sputtering technique and subsequently annealed from 200 to 500 °C. The structural, microstructural, electrical, and optical properties of as deposited and annealed SnO2 films were studied. The crystallinity degree of the films increased with annealing temperature. Photoluminescence (PL) measurements showed that the emission peaks have low intensity and are positioned at 535 nm (2.31 eV) and 605 nm (2.05 eV) in as deposited SnO2 films. The intensity of PL peak increases sharply with the increasing of annealing temperature. The as deposited films exhibited high electrical resistivity and low optical transmittance. After annealing at 500 °C, the electrical resistivity of the films decreased to the lowest value of 0.015 Ω cm, being the optical transmittance 90%.